Utilizing Waqf in Enhancing Islamic Finance Contributions for Overcoming Research and Innovation Funding Challenges in TVET Education Sector - Kamarzaman, Norshahira; Ahmad, Azlin Alisa; Muda, Mohd Zamro (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Waqf, Islamic perpetual charitable trusts, established in accordance with Sharia principles, have emerged as formidable financial instruments for sustaining diverse socio-educational initiatives throughout Malaysia. Technical and Vocational Education and Training (TVET), forming a critical component within the educational ecosystem, serves a fundamental function in developing skilled labor resources and responding to evolving industrial requirements. Financial limitations, especially regarding research advancement and innovation activities, present considerable obstacles for institutions delivering TVET programs, impeding technological progress and overall education quality. This investigation examines Islamic endowments as a strategic solution embedded within Islamic economic frameworks to address these financial constraints affecting research initiatives and innovation domains within TVET. By consolidating information from diverse sources, including scholarly articles, reports, and statistical analyses, this paper elaborates on the waqf concept in Islam, examines its contribution to economic development in Malaysia, and explores its potential as an innovative funding source for TVET research and innovation. The study also addresses management challenges associated with waqf assets and compares waqf with traditional educational endowments. The research findings underscore the critical importance of Islamic perpetual endowments as a strategic financial reservoir capable of mitigating resource deficiencies in Technical and Vocational Education research and innovation spheres, consequently strengthening human resource development while simultaneously advancing Islamic economic paradigms toward enhanced sustainability and broader inclusiveness. The findings of this study hold significant relevance for Indonesia, offering valuable insights into leveraging waqf for educational development in the world's largest Muslim-majority country, where TVET plays a crucial role in workforce development and economic growth.